KAJIAN INDEKS KEBAHAGIAAN KOTA SEMARANG 2017 - Dyah Maya Nihayah; Etty Soesilowati; Phany Ineke Putri (Jurnal Riptek, 2017)
Development progress has been seen more from economic indicators, such as economic growth and poverty reduction. The indicator is considered insufficient to describe the actual level of wellbeing. Economic indicators such as the value of HDI and the growth of GRDP per capita of Semarang City for the last five years continue to increase. However, the high economic growth of Semarang City leaves a gap in problems such as income distribution, poverty and other social problems. So this study aims to examine the index of community happiness Semarang City in 2017 compared with 2016. This study is a study where the data source obtained from a number of 404 samples taken by the method of three stages purposive random sampling. There are ten essential domains / variables that reflect the level of individual happiness, including: (1) health, (2) education, (3) household income, (4) environment and security, (5) family harmony, (6) social relations , (7) availability of free time, (8) Houses and Assets, (9) affection, and (10) happiness of life. The results showed that the happiness index of Semarang City in 2017 was 70.18. This value decreased from IK in 2016, amounting to 1.37 points. Although in general IK value fell, the variable of education and health performance better. This is seen from the value of happiness when the majority of the variable values fall, the variable of education and health, the value rises compared to 2016.